Simultaneous Quantitative and Qualitative Analysis of Flavonoids from Ultraviolet-B Radiation in Leaves and Roots of Scutellaria baicalensis Georgi Using LC-UV-ESI-Q/TOF/MS - Wen-Ting Tang; Min-Feng Fang; Xiao Liu; Ming Yue (Journal of Analytical Methods in Chemistry)
Scutellaria baicalensis Georgi is one of the most widely used traditional Chinese herbal medicines. It has been used for anti-inflammatory, anticancer, antibacterial activities, and so forth. Long-term enhanced ultraviolet-B (UV-B) radiation caused more effect on leaves than on roots of the plant. Liquid chromatography-ultraviolet detection coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (LC-UV-ESI-Q/TOF/MS) method was applied for simultaneous quantitative and qualitative analysis of flavonoids in leaves and roots of S. baicalensis by enhanced UV-B radiation. Both low-intensity radiation and high-intensity radiation were not significantly increaseing the contents of baicalin, wogonoside, and wogonin in roots. However different intensity of radiation has different effects on several flavonoids in leaves. Both low-intensity radiation and high-intensity radiation had no significant effect on contents of baicalin and tectoridin in leaves; the content of scutellarin was significantly decreased by low-intensity radiation; chrysin was detected in low-intensity radiation and high-intensity radiation, and chrysin content is the highest in low-intensity radiation, but chrysin was not detected in control group. Different changes of different flavonoids under enhanced UV-B radiation indicate that induction on flavonoids is selective by enhanced UV-B radiation.